Growth performance and ecological services evaluation of razor clams based on dynamic energy budget model. (15th March 2022) - Dong, Shipeng; Wang, Fang; Zhang, Dongxu; Yu, Liye; Pu, Weijia; Shang, Yankai
Abstract: Bivalve shellfish aquaculture has been proposed to abate eutrophication and increase carbon sink in integrated multi-trophic aquaculture ecosystems. An individual growth model for razor clams Sinonovacula constricta in an integrated aquaculture pond of Portunus trituberculatus – Penaeus japonicus – S. constricta was constructed based on dynamic energy budget (DEB) theory after parameter measurement and model validation. Goodness-of-fit indices (R-squared, mean difference, and absolute and relative root mean square error) showed that the DEB model accurately reproduced razor clam growth. The growth performance evaluation of razor clams under different environmental conditions showed that warming climate and food shortages inhibited the razor clam growth. The quantification results of ecological service showed that individual razor clam have the potential for nutrient (nitrogen and phosphorus) removal and CO2 fixation, but exhibit a source of CO2 in individual month. The possible applications and contribution of this aquaculture model in China are also discussed, and the assessment results can provide important support for the low carbon bivalve integrated aquaculture. Graphical abstract: Image 1 Highlights: Goodness-of-fit indices (R-squared, mean difference, and absolute and relative root mean square error) showed that the Sinonovacula constricta DEB model accurately reproduced razor clam growth. Net nutrient removal and CO2 fixation potential of razor clams were calculated within an integrated aquaculture pond condition. The assessment results are helpful in understanding the relationship between bivalves and the aquaculture environment, and provide guidance in maximizing the growth rate and ecosystem service value of aquaculture organisms.